022 Methoxyflurane: would giving the "Green Whistle" the green light benefit mountain casualties in Snowdonia?. (14th September 2011) - Burgess, S; Dykes, L
Abstract : Objectives and Backgrounds: Methoxyflurane, currently licensed only in Australasia, is a convenient, rapidly effective pre-hospital analgesic, although it achieves inferior pain reduction compared to intravenous morphine or intranasal fentanyl. Methoxyflurane in analgesic doses causes only minor, rapidly-reversible initial side effects, but repeated exposure can cause irreversible dose-dependent nephrotoxicity which limits duration of administration. In addition, there are occupational health concerns for personnel working in confined spaces. There are methoxyflurane proponents within the UK mountain medicine community, and we wondered whether methoxyflurane would be suitable for use by Mountain Rescue Team first-aiders treating casualties in Snowdonia if it became available in the UK. Methods: Our Mountain Medicine database (all casualties brought to Bangor ED following mountain incidents resulting in contact with Mountain Rescue Teams and/or RAF Search & rescue helicopter) was interrogated to determine how many trauma casualties could have been treated with methoxyflurane based upon the current Australasian product license indications/contraindications for the Penthox inhaler. Results: From 651 mountain casualties (January 2004–December 2010) sufficient data were available in 593 cases to identify 429 trauma casualties, 329 (77%) of which could theoretically have been treated with methoxyflurane. This was almost identical to those eligible to receive Entonox (76%). However, many cases would have required methoxyflurane for longer than the maximum 1-h because of prolonged scene/evacuation times in mountain settings. Conclusions: The maximum duration of methoxyflurane administration would be insufficient as the primary analgesic in many Snowdonia mountain casualties, however, the use of methoxyflurane as a holding measure while I/N diamorphine is being prepared may be a viable option. Mountain casualties are often treated in tent-like rescue shelters and enclosed helicopter fuselages, which may endanger rescuer health if methoxyflurane were used without adequate ventilation. Further work is required to elucidate how frequently low ambient temperature precludes the use of Entonox.